2005
DOI: 10.1590/s0103-50532005000300007
|View full text |Cite
|
Sign up to set email alerts
|

Bonding interactions of metal clusters [Mn (M= Cu, Ag, Au; n=1-4)] with ammonia. Are the metal clusters adequate as a model of surfaces?

Abstract: Cálculos de densidade funcional (B3LYP/LANL2DZ) para clusters metálicos de amônia foram efetuados para obter comprimentos de ligação, modos de estiramento vibracional M-N, energias de ligação, cargas atômicas de Mulliken e potenciais adiabáticos de ionização. Os resultados indicam que átomos de cobre formam ligações mais intensas com amônia do que com prata ou ouro. A interação da ligação Ag n com amônia é a mais fraca de todos os sistemas. A ligação das moléculas de amônia à clusters metálicos é comparável à … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…Several early investigations have demonstrated the reactivity of metal clusters with ammonia, an example of which is shown in Figure , where the interesting clusters Al 11 NH 3 – and Al 12 NH 3 – dominated the products. Theoretical calculations revealed that the presence of ammonia leads to geometric distortion of Al 12 – together with dissociation of the NH 3 molecule, the N and H atoms of which transfer onto the Al cluster, resulting in a reorganized minimum-energy structure.…”
Section: Reactivity Of Metal Clusters With Polar Moleculesmentioning
confidence: 99%
“…Several early investigations have demonstrated the reactivity of metal clusters with ammonia, an example of which is shown in Figure , where the interesting clusters Al 11 NH 3 – and Al 12 NH 3 – dominated the products. Theoretical calculations revealed that the presence of ammonia leads to geometric distortion of Al 12 – together with dissociation of the NH 3 molecule, the N and H atoms of which transfer onto the Al cluster, resulting in a reorganized minimum-energy structure.…”
Section: Reactivity Of Metal Clusters With Polar Moleculesmentioning
confidence: 99%
“…This distance is consistent with previously calculated bond lengths of amines on Ag surfaces. 59,60 The presence of a covalent Ag−N bond in this configuration is further supported by the charge transfer between Ag(100) and the amine, as indicated by the charge density difference relative to the potential of zero free charge (PZFC) (Figure 5a). A covalent bond is also supported by the observed population of Ag−N bonding orbitals below the Fermi level, as determined from crystal orbital Hamilton population analysis (SI, Figure S5).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…29 These are likely to originate from chelation of the metal surface by the lone electron pair on the nitrogen and the accompanying interfacial polarization effects. [44][45][46] Indeed, SKPM measurements on freshly evaporated gold coated by our interlayers presented dipole shis of À0.6 up to À0.7 eV, regardless of the chemical and physical (linear or three dimensional) structures of the interlayers. Similar to the gold interface, comparable interfacial dipoles are expected for the interfaces between the interlayer materials and the evaporated aluminium electrode.…”
Section: Resultsmentioning
confidence: 99%